A New Development of Modular-Approach Multi-Microcontroller Based Educational Training System - Selvakumar, Raja Saravana Kumar; Kamarul Hawari, Ghazali; Nik Mohd Kamil, Nik Yusof (2010)
In traditional Embedded Control Technology courses, students learn to develop assembly language programs to control peripherals, handle interrupts, and perform I/O operations is often difficult because students find the subject rather abstract when presented in a lecture format. In fact this Embedded Controller Technology (ECT) course is a compulsory course in any electrical or electronic field of engineering. This paper aims to describe development of a flexible multi-microcontroller training system based on 8-bit microcontroller in Microchip, Motorola and Intel family. For this reason, the multi-microcontroller based development project will be designed to be as a learning tool for those who intend to learn microcontroller. With an extensive a development board, it could let the user to get start with their microcontroller application efficiently. In addition, it is further boosted by the introduction of Integrated Development Environment (IDE) features in order to create user-friendly environment. By using this system, users are exposed to practical experience of the microcontroller and provide an easy path to learn this intelligent electronic device in short time. Without wasting too much time in preparing prototype circuit is one of the advantages by using a development board. In this respect, this multi-microcontroller Training System would be applicable for education and expose the electrical engineering students to the understanding fundamental of microcontroller in electronic design field. Keywords:, Educational, MCS51 microcontroller, HC11 microcontroller, PIC microcontroller